Air-Way Wirl-A-Way Insector - Science History Institute (2018)
Air-Way brand pesticide vacuum sprayer with glass jar and box. A. Glass jar with small label. Text reads "Moth Control Especially Prepared For Use with Wirl A Way Insector." B. Metal, blue Wirl-A-Way sprayer with two hose attachment areas. C. Box for Air-Way Wirl-A-Way Insector Unit. Blue text on yellow background with sprayer graphic. Instructions listed.
Keywords: Pests--Control; Pesticides; DDT (Insecticide); Insecticides